The triadic relation of game, an interpretation of three human activities (Agora for Physical Education and Sport, 2018)
This paper tries to verify whether the so-called 'tricky triad' (Suits, 1988), or deceptive triad, behaves like a true relational triad. All this is verified from a communication and the analysis of decisions theory perspective through a ludic behavior model of a chase game, which starts with an unequal distribution of forces. It is debated if the concepts of play-game-sport truly respond to the establishment of a relational triad that will increase our understanding of the behaviors within these activities. The logic of situations is developed, justifying the decisions of the players. The emergence of situational paradoxes in the interrelationships between the three concepts is confirmed.
Keywords: Play; triad; sport; philosophy of sport; ambivalence